Discovery of novel dipeptidyl peptidase-IV inhibitory peptides derived from walnut protein and their bioactivities in vivo and in vitro - Xinxin Mu; Dan Li; Ran Xiao; Kaifang Guan; Ying Ma; Rongchun Wang; Tianjiao Niu (Current Research in Food Science)
The inhibition of dipeptidyl peptidase IV (DPP-IV) has been regarded as a major target for treating type-2 diabetes (T2D). Food-derived peptides are a great source of DPP-IV inhibitory peptides. In this study, we utilized walnut protein as the raw material and hydrolyzed it using four different proteases. The trypsin hydrolysate exhibited the highest DPP-IV inhibitory activity. A DEAE-52 anion exchange column and a Sephadex G-25 gel filtration column were used to sequentially separate and purify the enzymatic hydrolysates. Mass spectrometry identified 117 peptide sequences, of which LPFA, VPFWA, and WGLP were three highly active DPP-IV inhibitory peptides. Molecular docking results revealed that three peptides primarily bind tightly to DPP-IV through hydrogen bonds and van der Waals forces. The inhibitory activity and absorption transport of the peptides were examined using a Caco-2 cell model. LPFA, VPFWA, and WGLP could cross the Caco-2 cell monolayer intact, with in situ IC50s of 267.9 ± 7.2 μM, 325.0 ± 8.4 μM, and 350.9 ± 8.3 μM, respectively. Oral glucose tolerance tests (OGTT) demonstrated that the three inhibitory peptides significantly improved glucose metabolism in normal ICR mice. This study establishes a theoretical basis for the high-value utilization of walnuts and the therapeutic treatment of T2D.